Kaombo: Local wisdom regarding forest conservation system among the rongi indigenous people in South Buton - Munafi, La Ode Abdul; Malim, Dinna Dayana La Ode; Tahara, Tasrifin (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2022)
This article describes a local wisdom regarding forest conservation system called kaombo in the Rongi indigenous people in South Buton Regency, Indonesia. This is qualitative research with an ethnographic design. Data collection was carried out through in-depth interviews, participant observation, and documentation. Data analysis was carried out in a descriptive-qualitative ways using data reduction, presentation, and verification. The results of the research show that kaombo is a cultural institution that contains instrumental values to prevent forests from threats such as human overexploitation. The kaombo forest conservation system is reflected in the local knowledge of the Rongi indigenous people about forests and agricultural land use patterns. The principles of kaombo include forest sustainability, enforcement of customary sanctions for violations, and utilization of kaomboforest resources. Kaombo allows the carrying capacity of forest areas to be maintained.